Procedure for Distribution Permits for Traditional Medicines Products for the Convenience of Traditional Medicine Micro Business and Traditional Medicine Small Business in North Maluku (Agrikan Jurnal Agribisnis Perikanan, 2024)
The increasing use of traditional medicinein the country has encouraged an increase in Micro and Small Enterprises(MSMEs)engaged in traditional medicine, including Micro Traditional Medicine Enterprises (UMOT) and Small Traditional Medicine Enterprises (UKOT) which have begun to emerge in society. Based on survey, there are 11 MSMEs that produce essential oils for traditional medicine and only 27,3% od MSMEs meet the Good Manufacturing Practices for Traditional Medicine (CPOTB) stage 1. One of the obligation that must be fulfilled by UMOT or UKOT in distributing the traditional medicine they produce is to have a distribution permit number for the medicine. In managing adistribution permit for traditional medicine, business actors must meet severat requirments and go through several stages explained in this article. It is estimated that business actors, both UMOT and UKOT, find it easier to manage a distribution permit for traditional medicine.
Keywords: Obat tradisional; Izin edar; UMOT; UKOT